2018
DOI: 10.1175/jas-d-17-0352.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cold Pools in Tropical Oceanic Convective Systems

Abstract: The processes governing organized tropical convective systems are not completely understood despite their important influences on the tropical atmosphere and global circulation. In particular, cold pools are known to influence the structure and maintenance of midlatitude systems via Rotunno–Klemp–Weisman (RKW) theory, but cold pools may interact differently with tropical convection because of differences in cold pool strength and environmental shear. In this study, the role of cold pools in organized oceanic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 81 publications
(85 reference statements)
9
36
0
Order By: Relevance
“…As in Haerter et al (), the present tracking method exploits the fact that CPs generally are confined by a band of convergence, using Lagrangian tracers. Allowing advection in all three spatial dimensions, Lagrangian particles were previously applied to analyze CPs (Grant et al, ; Torri & Kuang, ; Torri et al, ). To prevent mixing of particles into the upper boundary layer, the current particle‐based method demands that tracer particles are constrained to travel only horizontally (Figure a,b).…”
Section: Introductionmentioning
confidence: 99%
“…As in Haerter et al (), the present tracking method exploits the fact that CPs generally are confined by a band of convergence, using Lagrangian tracers. Allowing advection in all three spatial dimensions, Lagrangian particles were previously applied to analyze CPs (Grant et al, ; Torri & Kuang, ; Torri et al, ). To prevent mixing of particles into the upper boundary layer, the current particle‐based method demands that tracer particles are constrained to travel only horizontally (Figure a,b).…”
Section: Introductionmentioning
confidence: 99%
“…To better clarify the role of cold pools in convective organization, we have performed “no‐cold pool” experiments by adjusting the Thompson microphysics. The most common way to remove cold pools in model experiments is to turn off the evaporation of rain (such as Grant et al., 2018; Jeevanjee & Romps, 2013; Khairoutdinov & Randall, 2006). That method should remove the cold air, but downdrafts below the convective updrafts could still exist because the downward dynamic pressure gradient force as well as hydrometeor loading effect is not removed.…”
Section: ‐08‐10 Casementioning
confidence: 99%
“…Shear in the middle and upper‐troposphere is also important (e.g., Parker & Johnson, 2000). However, in situations with weaker shear or weaker cold pools, other mechanisms, like gravity waves, can have a prominent impact on MCS dynamics (e.g., Lane & Moncrieff, 2015, hereafter LM15; Grant et al., 2018, 2020). In this study, a new paradigm for convective organization is introduced, whereby stratospheric wind shear is shown to influence MCSs through gravity wave‐convection interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Lane and Zhang (2011) showed that gravity waves and mesoscale cloud populations become dynamically coupled, with the gravity waves feeding back on the convective clouds through transient ascent and descent that modifies their morphology. Grant et al (2018Grant et al ( , 2020 demonstrated that when cold pools are weak, gravity waves can help maintain long-lived mesoscale systems. In this study, idealized simulations (similar in concept to Grant et al, 2018Grant et al, , 2020Lane & Zhang 2011;Tulich & Mapes, 2008;LM15 and others) are used to further explore gravity wave-convection coupling.…”
mentioning
confidence: 99%